INTERNALISASI NILAI KARAKTER KEAGAMAAN DAN KEBANGSAAN PADA SISWA DI SEKOLAH BERBASIS PONDOK PESANTREN - Uan Abdul Hanan; Mulyoto Mulyoto; A. Mufrod Teguh Mulyo (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This study aims to analyze the results of the internalization of religious and national character values in students at Islamic boarding schools at VIP Ma'arif NU Vocational School 1 Kemiri Kutoarjo Purworejo and Darul Hikmah Kutoarjo Purworejo High School. This research is qualitative research that is used to examine the condition of natural objects where the researcher is a key instrument with the stages of Data Reduction, Data Presentation, and Drawing Conclusions. The findings in this study are that the theory of value internalization which consists of three stages, namely internalization, transaction, and trans-internalization, needs to be developed with the initial stage in the form of a student's identity declaration which has a certain character which is marked by the imposition of attributes that characterize a particular community. This declaration is the foundation for further strengthening the process of internalizing character values